(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2019)
In this paper we solve two instances of the main problem in coding theory for linear codes of dimension 5 over F_4. We prove the nonexistence of [395,5,295]_4- and [396,5,296]_4-codes which implies the exact values n_4(5,295)=396 and n_4(5,296)=397. As a by-product, we characterize the arcs with parameters (100,26) in PG(3,4).